Sistem Monitoring Ruang Server Berbasis IoT Menggunakan Komunikasi Lora Ebyte E32 - Wibowo, Irwan Setyo; Adit, Muhammad Aditiya Firdaus; Laksana, Teguh Teuja (APIC, 2023)
The critical issue in server room management, emphasizing the potential damage caused by elevated temperatures to hardware within the server room environment. The proposed solution involves leveraging Internet of Things (IoT) technology, specifically utilizing LoRa (Long Range) communication, to monitor key environmental parameters such as temperature, humidity, and fire incidents. The sensors chosen for this purpose are the DHT11 for measuring temperature and humidity, and a Fire sensor for detecting potential fire hazards. The research focuses on three main aspects: testing the transmission distance, evaluating data delivery, and integrating sensor data into the Blynk dashboard, which serves as the central monitoring system. The testing process involves assessing the performance of the system under different conditions. Firstly, the transmission distance is tested, presumably to determine the maximum distance over which the sensors can reliably communicate with the monitoring system. Secondly, data delivery is examined, likely to ensure the timely and accurate transfer of information from the sensors to the monitoring dashboard. Lastly, the research involves the integration of sensor data into the Blynk dashboard, indicating a comprehensive approach to visualizing and interpreting the collected data. The results of the testing reveal that the optimal performance is achieved when the transmission distance is below 600 meters. This distance is achieved using a 5dBi antenna, connected to the Blynk dashboard, which is identified as the preferred monitoring system. The findings suggest that this IoT-based solution utilizing LoRa communication and specific sensors effectively addresses the challenges associated with server room management, providing a reliable and real-time monitoring mechanism to mitigate potential hardware damage due to environmental factors.